2023
DOI: 10.1186/s12966-023-01493-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of habit formation interventions on physical activity habit strength: meta-analysis and meta-regression

Haoming Ma,
Aoqi Wang,
Runyuan Pei
et al.

Abstract: Background Interventions aimed at promoting physical activity (PA) behavior through habit formation pathways are gaining popularity, as they differ from conventional interventions that rely on intention pathways. Past research has established a positive correlation between PA habits and behavior. However, the efficacy of current interventions designed to form PA habits and improve PA automaticity is not yet fully ascertained. Additionally, the intervention components that significantly impact t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
(74 reference statements)
1
3
0
Order By: Relevance
“…The significant relationship found in previous studies 12 , 13 between habit and PA in adolescence is confirmed. In fact, in our research, habit appears to be the M-PAC indicator most significantly correlated to the amount of both moderate and vigorous physical activity.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The significant relationship found in previous studies 12 , 13 between habit and PA in adolescence is confirmed. In fact, in our research, habit appears to be the M-PAC indicator most significantly correlated to the amount of both moderate and vigorous physical activity.…”
Section: Discussionsupporting
confidence: 80%
“…Habit formation interventions and habit interruption have been demostrated to influence PA (fostering or reducing it) during adolescence 12 , 13 . Habit has been characterized as an important predictor of changes in MVPA in pandemic restrictions 14 , and it has been seen as salient predictor of adolescent PA 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite arguments in favor of using reminders as a strategy to support habit formation, a recent meta-regression of ten randomized controlled trials (RCTs) found no significant positive effect of the behavior change technique (BCT) prompts and cues (i.e., the broader category of environmental stimuli, including reminders, aiming at prompting or cueing the behavior; Michie et al, 2013) on habit formation in physical activity (Ma et al, 2023). These null findings might have theoretical and methodological explanations.…”
Section: Intervention Strategies To Support Habit Formationmentioning
confidence: 99%
“…7) Assist I@R in developing healthy habits instead of behavior change. There is a small, but increasing literature demonstrating that habit formation, i.e., repeating the same behavior in the same context until it becomes automatic and effortless, may take longer to acquire but requires less ongoing effort to sustain [8]. 8) An experimentation framework that allows testing of potential interventions for efficacy and effectiveness for different segments/populations of patients.…”
Section: What Needs To Be True?mentioning
confidence: 99%